A kind of grease prepared by using metal salt and preparation method thereof
By using components such as metal salts, adhesives and gelling reagents in the grease, the problems of cumbersome preparation process and poor performance of traditional soap-based greases are solved, and the high performance and green preparation of greases are achieved.
Patent Information
- Application Number
- CN202411134772.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the prior art, the soap-based grease prepared by the traditional method is complicated in the process and cannot effectively ensure the stability, high and low temperature resistance, oxidation resistance and corrosion resistance of the grease.
Lubricating grease prepared using metal salts, adhesives and gelling reagents enhances the interaction force between molecules by changing the type and dosage of base oil, using metal salts of multiple components, and introducing phosphorus-containing acrylate adhesives and modified methylcellulose.
The obtained grease has better comprehensive properties, high drop point, low oil separation in the steel mesh, good acid resistance and mechanical stability, and the preparation process is green, simplified and energy-saving.
Smart Images

Figure CN119040051B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating grease, in particular to a lubricating grease prepared by using a metal salt and a preparation method thereof. Background Art
[0002] In 1400 BC, the ancient Egyptians mixed fat and lime as a lubricant to prepare the earliest "calcium-based grease", which is also a soap-based grease. At present, the proportion of soap-based greases at home and abroad is far greater than that of non-soap-based greases, especially lithium-based greases.
[0003] Soap-based greases have different properties because they contain different metals. For example, sodium-based greases are made by reacting fatty acids with alkaline sodium compounds. Alkaline sodium compounds have strong reactivity, are easy to form salts, and have low temperatures. The preparation process is relatively simple, but their use temperature is also low and they are easy to emulsify. Some metal compounds with weaker alkalinity have increased difficulty in reacting with fatty acids and are difficult to saponify into grease. Usually, strong alkaline compounds need to be added for saponification to obtain grease, and the equipment requirements are relatively high. General manufacturers do not have these types of products.
[0004] Patent CN116515545B discloses "a kind of grease and its preparation method and use". A tackifier is added to the base oil to improve the viscosity index, colloidal stability and water-resistant performance of the grease. The tackifier is ApaSynTM series of high-viscosity metallocene polyalphaolefins. The tackifier given in the comparative example is methacrylate copolymer and ethylene propylene copolymer. The low-temperature Brookfield viscosity of the grease prepared in the comparative example is improved, the cone penetration is reduced, the pour point is reduced, and the high temperature and low temperature performance are poor.
[0005] Patent CN115895761B discloses "a high temperature resistant universal extreme pressure lubricating grease", which is obtained by adding modified graphene to base oil and mixing it with soap-based thickeners, antioxidants and dispersants. The grease has good high temperature resistance, high extreme pressure and anti-wear properties, and high temperature resistance. However, there is no cross-linking or penetration between the components, and the obtained grease has poor stability and high oil separation.
[0006] In order to improve the adhesion and stability of grease and promote the formation of a stable colloidal structure, patent CN110616102B discloses "a composite grease and its preparation method", by adding modified cellulose nanocrystals to the base oil, which act as crystal nuclei to allow the thickener to adhere to the surroundings to form a colloid-like structure, thereby promoting the formation of the grease network structure. The modified cellulose nanocrystals are evenly dispersed in the grease, making the grease more stable, but the grease has poor high temperature resistance and poor water resistance.
[0007] Good antioxidant stability can extend the service life of grease. Patent CN113913228B discloses "an antioxidant composition for lithium-based grease". The antioxidant composition is composed of amines or phenols and copper dimethyldithiocarbamate. The final bearing grease life test results show good antioxidant effect. However, organic antioxidants have a short service life and become ineffective after oxidation, which is not conducive to improving the service life of grease. Copper dimethyldithiocarbamate is prone to aggregation and poor dispersion in grease under the action of mechanical external forces, which affects the performance of antioxidant properties.
[0008] In the prior art, the preparation process of soap-based grease prepared by traditional methods is cumbersome, and the stability, high and low temperature resistance, oxidation resistance, corrosion resistance and other properties of the grease cannot be guaranteed.
[0009] Therefore, a lubricating grease prepared by using metal salt and a preparation method thereof are proposed. Summary of the invention
[0010] In view of the problems existing in the prior art, the purpose of the present invention is to provide a grease prepared by metal salt and a preparation method thereof. The grease adopts Class II base oil, metal salt, adhesive and gelling agent. In addition to ensuring the normal production of the grease, it can improve the colloid stability, mechanical stability, roller stability and operating temperature of the grease and has broad application prospects.
[0011] In order to achieve the above technical objectives, the inventors combined the lubrication theme of "safety, simplicity and energy saving" and, under the premise of ensuring the normal production of grease, selected some adhesives and gelling agents to prepare several soap-based greases mainly based on metal salts to meet the mechanical lubrication requirements under heavy load, high water and high-speed environments, thereby extending the service life of the equipment, saving energy and reducing the cost of use.
[0012] To achieve the above object, the present invention provides the following technical solutions:
[0013] In one aspect, the present invention provides a lubricating grease prepared using a metal salt, characterized in that the lubricating grease is prepared from the following components in parts by weight:
[0014]
[0015] The adhesive comprises phosphorus-containing acrylate adhesive, trimethyl phosphate and triaminotriphenylthiophosphate; the phosphorus-containing acrylate adhesive is prepared from methyl methacrylate, acrylic acid phosphate, acrylic acid and acrylic acid ester;
[0016] The adhesive comprises structures as shown in I and II:
[0017]
[0018] wherein R1 is one of hydrogen and methyl; R2 is one of hydrogen and methyl; X is a polymer of the methyl methacrylate, the acrylic acid phosphate, the acrylic acid and the acrylic acid ester;
[0019] Where R3 is C 10 , C 12 , C 18 One of alkyl, methyl phosphate, octyl phosphate, and nonyl phosphate;
[0020] The gelling agent comprises carboxymethyl cellulose, modified methyl cellulose and silane; the modified methyl cellulose is prepared from sodium carboxymethyl cellulose, epoxy resin, organic acid, silicate and deionized water;
[0021] The structure of the sodium carboxymethyl cellulose is shown in III; the structures of the silane and the silicate are shown in IV;
[0022]
[0023] Wherein R4 is one of methoxy, ethoxy, vinyl, octyl, and octadecyl; R5, R6, and R7 are each one of methyl and ethyl;
[0024] The performance improvers include antioxidants, anti-wear agents and anti-corrosion agents;
[0025] The antioxidant includes antioxidant 1 and antioxidant 2;
[0026] The anti-wear agent comprises nano copper emulsion, nano tin self-repairing material, boron nitride and sodium naphthenate.
[0027] Preferably, the base oil is selected from one of 350SN and 500SN; the base oil is a Class II base oil; wherein the base oil meets the indicators in the following table:
[0028] project index Test Method <![CDATA[Kinematic viscosity / (100 °C, mm 2 ·s -1 )]]> 7-17 GB / T265 Flash point / (open, ℃) ≥100 GB / T3536 Pour point / ℃ ≤-10 GB / T3536 Viscosity Index ≥80 GB / T2541
[0029] The metal salt is one or a combination of two or three of lithium stearate, 12-hydroxylithium stearate, sodium 12-hydroxystearate, sodium stearate, calcium stearate, calcium 12-hydroxystearate, sodium palmitate, calcium palmitate, sodium cyclopentaneate, calcium cyclopentaneate, calcium borate, calcium acetate, barium stearate, and barium 12-hydroxystearate.
[0030] Preferably, the acrylic acid ester is any one of decyl acrylate, dodecanol acrylate and octadecyl acrylate; the acrylic acid phosphate is any one of methacrylic acid phosphate, polyethylene glycol methacrylic acid phosphate, 10-(2-methacryloyloxy)monodecyl phosphate and 2-methyl-2-acrylic acid-2-(phosphonooxy)ethyl ester; in terms of molar mass ratio, the methyl methacrylate: the acrylic acid: the acrylic acid: the acrylic acid phosphate is 1:1:1-1.2:1; the total amount of the methyl methacrylate, the acrylic acid, the acrylic acid and the acrylic acid phosphate is 94-125 parts.
[0031] Preferably, the silane is any one of n-octyltriethoxysilane, vinyltrimethoxysilane and triethoxyoctadecylsilane; the amount of the silane is 0.2-0.4 parts; the epoxy resin is any one of RDGE and BADGE; the amount of the epoxy resin is 22-34 parts; the organic acid is any one of glutaric acid, azelaic acid, sebacic acid and hexadecanedioic acid; the amount of the organic acid is 13-28 parts; the silicate is any one of methyl silicate and ethyl silicate; the amount of the silicate is 15-21 parts; the amount of deionized water is 4.0-4.2 parts.
[0032] Preferably, the antioxidant one is obtained by loading ionic liquid with nano-titanium dioxide; the dosage of the antioxidant one is 0-0.7 parts; the ionic liquid is any one of [C8MPy]PF6, [C16Mim]PF6, [C16Mim]BF4 and [C12M2Im]NTf2; the dosage ratio of the nano-titanium dioxide and the ionic liquid is 4-19:1-3; the dosage of the antioxidant two is 0.3-1 parts.
[0033] Preferably, the second antioxidant is any one of butylated hydroxymethoxybenzene, N-phenyl-α-naphthylamine, alkylated phenyl-α-naphthylamine, benzotriazole derivatives, thiadiazole derivatives and butylated hydroxymethoxybenzene.
[0034] Preferably, the corrosion inhibitor is any one of sodium petroleum sulfonate, imidazoline cyclohexane acid, N-acyl sarcosine and sodium benzoate.
[0035] Preferably, the preparation method of the nano copper emulsion is as follows: 10 parts of the nano copper emulsion is added into a ball mill, 70 parts of the methacrylate copolymer emulsion is added thereto, and the nano copper emulsion is obtained by grinding at a rotation speed of 300 rpm for 5 hours.
[0036] Preferably, the preparation method of the nano-tin self-repairing material is as follows:
[0037] The cellulose nanocrystals are dispersed in deionized water and anhydrous ethanol, and stirred to obtain a cellulose nanocrystal suspension; the temperature is raised to 60°C, and sodium butyrate is added and stirred, and the pH is adjusted to 4.5 when the temperature drops to 25°C, and distilled water is used for dialyzing and freeze-drying to obtain freeze-dried cellulose nanocrystals; the freeze-dried cellulose nanocrystals are dispersed in deionized water, the temperature is raised to 90°C, and potassium stannate trihydrate is added, and the reaction is stirred for 3 hours to obtain a tin-containing cellulose nanocrystal solution; after the tin-containing cellulose nanocrystal solution drops to 25°C, sodium periodate, stirring for 24 hours under light-proof conditions, then adding ethylene glycol solution, and dialyzing to obtain a tin-containing oxidized cellulose nanocrystal solution; adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide to the tin-containing oxidized cellulose nanocrystal solution, and then adding 7.5-9.0 parts of 5-(2-amino-ethyl)-2-hydroxybenzoic acid to obtain a graft precursor; raising the temperature of the graft precursor to 50° C., stirring and reacting under nitrogen protection for 10 hours, and dialyzing through a dialysis bag to obtain a graft solution;
[0038] Dissolving chitosan in an acetic acid solution under stirring to obtain a chitosan solution; dissolving the N-hydroxysuccinimide and the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide in methanol to obtain a catalytic mixed solution; adding the catalytic mixed solution to the chitosan solution, and then adding 6.3-7.3 parts of phenylboric acid, raising the temperature to 80° C., and stirring for 20 hours to obtain a phenylboric acid chitosan solution; dialyzing and drying the phenylboric acid chitosan solution to obtain phenylboric acid chitosan; the phenylboric acid is any one of 4-carboxynaphthalene-1-boric acid, 4'-(carboxy)biphenyl-4-boric acid and 3,5-diboric acid benzoic acid;
[0039] The phenylboronic acid chitosan is added into deionized water, and the temperature is raised to 80° C. to obtain solution 1; the graft solution is added into solution 1, and polyvinyl alcohol is added and mixed evenly to obtain solution 2; the solution 2 is stirred and reacted for 7 hours, and after cooling, it is filtered and dried to obtain the nano-tin self-healing material.
[0040] On the other hand, the present invention provides a method for preparing grease using metal salts, characterized in that the preparation method comprises the following steps:
[0041] S1 In a normal pressure reactor, part of the base oil and the metal salt are mixed uniformly, and stirred at 500 rpm for 2 h to obtain a uniform emulsion 1;
[0042] S2: adding the remaining base oil into another reactor, adding polytetrafluoroethylene, an adhesive and a gelling agent to obtain a mixture; stirring the mixture for 2 hours to obtain a uniform emulsion 2;
[0043] S3: transferring the uniform emulsion 1 to the uniform emulsion 2 to obtain a mixed emulsion; raising the temperature of the mixed emulsion to 60° C., stirring at a speed of 800 rpm for 3 hours, and performing a cross-linking reaction to obtain a uniform emulsion;
[0044] S4: heating the uniform emulsion to 200° C. and degassing for 10 min to obtain a degassed emulsion;
[0045] S5: cooling the degassed emulsion to 85° C., maintaining the temperature for 0.5 h, adding a performance improver, and obtaining a soap-based grease precursor;
[0046] S6, grinding the soap-based grease precursor in a three-roll mill for three times to prepare the grease prepared from the metal salt;
[0047] The grease comprises the base oil, the metal salt, the polytetrafluoroethylene, the adhesive, the gelling agent and the performance improver; the grease is brown and transparent in appearance; the working cone penetration of the grease is 240-278 / 0.1mm, the dropping point is 95-275°C, and the oil separation of the steel mesh is 1.81%-4.55%; by adding the adhesive, the working cone penetration of the grease is 215-349 / 0.1mm, the corrosion resistance test is qualified, and the grease maintains the grease properties within 18-29 days after being soaked in weak acid; by adding the gelling agent, the dropping point of the grease is 226-314°C, the oil separation of the steel mesh is 1.48%-4.62%, and the water loss is 0.27%-1.29%; under the test condition of 180°C, the PDSC oxidation induction time of the grease is 16.9-35.8min; the P B The wear force is 491-981N, and the wear scar diameter is 0.35-0.62mm.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] 1. Unlike the traditional preparation of lithium-based, calcium-based and barium-based greases, the present invention uses weakly alkaline metal salts as thickeners to thicken the base oil into grease. By changing the type and amount of base oil, using metal salts of multiple components, changing the type and amount of each component, and introducing adhesives and gelling agents, the interaction between molecules is enhanced, so that the obtained grease has better comprehensive properties than the soap-based grease prepared by traditional methods, with a high dropping point, less oil separation on the steel mesh, better acid resistance and good stability. At the same time, the preparation process is green, simplified and energy-saving.
[0050] 2. The present invention first uses acrylate, acrylic acid and phosphorus-containing acrylate as raw materials to prepare phosphorus-containing acrylate adhesive, which is used in combination with phosphate and triaminotriphenylthiophosphate as a thickener, and then polytetrafluoroethylene is added. The obtained grease has good working cone penetration and good corrosion resistance.
[0051] 3. By dispersing methyl cellulose in water to form a cellulose solution, the epoxy resin opens the epoxy bond under high temperature conditions and condenses with the hydroxyl groups on the surface of the methyl cellulose, and then the epoxy resin and the methyl cellulose are connected by chemical bonds, one end of the organic acid is connected to the methyl cellulose, and the other end is coupled with the hydrolyzed silicate to form modified methyl cellulose. The modified methyl cellulose and n-octyl triethoxysilane are used as gelling agents together, and the obtained grease has a high dropping point, less oil separation from the steel mesh, and low water loss. The grease has good mechanical stability and can meet high temperature conditions.
[0052] 4. Inorganic antioxidants are obtained by loading ionic liquids on nano-titanium dioxide, and used in combination with organic antioxidants as additives for greases, which have good antioxidant properties. By loading ionic liquids on mesoporous nano-titanium dioxide, on the one hand, the specific surface area of the antioxidant is increased, and free radicals are more easily captured. On the other hand, the cation and anion structures in the ionic liquid further enhance the antioxidant effect. Compared with organic antioxidants, titanium dioxide loaded with ionic liquids has a stable and lasting antioxidant effect, and the two synergistically improve the antioxidant properties of greases.
[0053] 5. The present invention uses nano copper emulsion, nano tin self-healing material and performance improvers such as boron nitride in combination, and the obtained grease has good extreme pressure and wear resistance. After the homemade nano tin self-healing material is damaged by mechanical action, the damaged hydrogen bonds re-form new hydrogen bonds with chitosan and cellulose nanocrystals, and the metal coordination bonds formed by tin also improve the stability of the system, thereby improving the extreme pressure and wear resistance of the grease. The prepared grease has a more stable colloidal structure and better performance, which significantly extends the service life of the equipment, thereby reducing the cost of use. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The process flow chart of the lubricating grease prepared by the metal salt of the present invention;
[0055] Figure 2 This is a SEM image of the grease prepared in Example 2 of the present invention;
[0056] Figure 3 This is a SEM image of the grease prepared in Example 8 of the present invention;
[0057] Figure 4 This is a SEM image of the grease prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0058] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] See also Figures 1 to 4 The present invention provides a grease prepared by using a metal salt and a preparation method thereof, and the technical scheme is as follows:
[0060] The material information used in the preparation process of the embodiment is as follows:
[0061] BADGE2,2-bis-(4-glycolylaminophenyl)propane CAS1675-54-3; RDGE resorcinol diglycidyl ether CAS 101-90-6; 5-(2-amino-ethyl)-2-hydroxybenzoic acid, CAS: 4900-26-9; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, CAS: 1892-57-5; N-hydroxysuccinimide, CAS: 6066-82-6; 4-carboxynaphthalene-1-boric acid CAS: 332398-57-9; 4'-(carboxy)biphenyl-4-boric acid, CAS: 872341-95-2; 3,5-diboronic acid benzoic acid, CAS: 271256-06-5; n-octyltriethoxysilane, CAS: 2943-75-1; vinyltrimethoxysilane, CAS: 2768-02-7; triethoxyoctadecylsilane, CAS: 7399-00-0;
[0062] Nano-titanium dioxide CAS: 13463-67-7 and nano-copper were purchased from Xianfeng Nanomaterial Technology Co., Ltd.;
[0063] Thiadiazole derivatives, CAS: 4865-02-5; T551 benzotriazole derivatives were purchased from Jinzhou Shengda Chemicals Co., Ltd.;
[0064] Sodium petroleum sulfonate T702 was purchased from Hubei Kewode Chemical Co., Ltd.;
[0065] Cyclohexanecarboxylic acid imidazoline was purchased from Keling Chemical Co., Ltd.;
[0066] Ionic liquids [C8MPy]PF6, [C16Mim]PF6, [C16Mim]BF4, and [C12M2Im]NTf2 were purchased from Xi’an Qiyue Biotechnology Co., Ltd.;
[0067] Methacrylate copolymer emulsion Acronal PA510 was purchased from BASF China Ltd.;
[0068] The reagents used in the present invention are analytically pure, and other substances and reagents are conventional commercial products unless otherwise specified.
[0069] Examples 1-17
[0070] S1. In a normal pressure reactor, 50 parts of base oil 500SN and 10 parts of lithium stearate were mixed evenly, and stirred at 500 rpm for 2 h to obtain a uniform emulsion 1;
[0071] S2, adding the remaining 36 parts of base oil 500SN into another reactor, adding 0.2 parts of polytetrafluoroethylene, 0.8 parts of triethyl phosphate adhesive and 1 part of carboxymethyl cellulose gelling agent to obtain a mixture; stirring the mixture for 2 hours to obtain a uniform emulsion 2;
[0072] S3, transferring the uniform emulsion 1 to the uniform emulsion 2 to obtain a mixed emulsion; raising the temperature of the mixed emulsion to 60° C., stirring at a speed of 800 rpm for 3 hours, and performing a cross-linking reaction to obtain a uniform emulsion;
[0073] S4, heating the homogeneous emulsion to 200°C and degassing for 10 minutes to obtain a degassed emulsion;
[0074] S5, cooling the degassed emulsion to 85°C, maintaining the temperature for 0.5h, adding a performance improver (0.5 parts of nano copper emulsion, 0.5 parts of boron nitride, 0.5 parts of N-phenyl-α-naphthylamine and 0.5 parts of cyclopentane acid imidazoline) to obtain a soap-based grease precursor; the nano copper emulsion boron nitride is an anti-wear agent; the N-phenyl-α-naphthylamine is an antioxidant; and the cyclopentane acid imidazoline is a corrosion inhibitor;
[0075] S6. Grind the soap-based grease precursor in a three-roll mill for three times to prepare a soap-based grease prepared with a metal salt.
[0076] The preparation method of the nano copper emulsion is as follows: 10 parts of nano copper are added into a ball mill, 70 parts of methacrylate copolymer emulsion are added thereto, and the nano copper emulsion is obtained by grinding at a rotation speed of 300 rpm for 5 hours.
[0077] The detailed information of the preparation process of Example 1 and other examples is shown in Table 1.
[0078] Table 1 Changes in base oil and metal salt addition process
[0079]
[0080]
[0081] Comparative Example 3
[0082] S1. In a normal pressure reactor, 60 parts of base oil 500SN are heated to 60° C. to obtain a heated base oil; 8 parts of 12-hydroxystearic acid are added to the heated base oil and stirred to obtain a mixed oil;
[0083] S2, dissolving lithium hydroxide in deionized water to obtain a lithium hydroxide solution 1; the mass ratio of lithium hydroxide to deionized water is 1.3:15; adding the lithium hydroxide solution 1 to the mixed oil to obtain the oil to be saponified;
[0084] S3, when the temperature of the saponified oil is raised to 90°C, stir and react for 2 hours to obtain saponified fat 1;
[0085] S4, heating the saponified fat 1 to 110°C to remove the water in the system; then adding lithium hydroxide solution 2 to adjust the pH of the system to 8, to obtain saponified fat 2; the mass ratio of lithium hydroxide to deionized water in the lithium hydroxide solution 2 is 0.2:5;
[0086] S5, heating the saponified fat 2 to 210°C at a heating rate of 1.2°C / min, then adding the remaining 28 parts of base oil for cooling, and when the temperature drops to 130°C, maintaining the constant temperature for 0.5h to obtain the saponified fat; cooling the saponified fat to 90°C, and then adding a performance improver (1 part of nano copper emulsion, 0.5 parts of N-phenyl-α-naphthylamine and 0.5 parts of cyclohexane acid imidazoline) to obtain a lithium-based grease precursor;
[0087] S6. Grind the lithium-based grease precursor in a three-roll mill for three times to prepare a lithium-based grease.
[0088] Comparative Example 4
[0089] S1. In a normal pressure reactor, 60 parts of base oil 500SN are heated to 60° C. to obtain a heated base oil; 9 parts of 12-hydroxystearic acid are added to the heated base oil and stirred to obtain a mixed oil;
[0090] S2, adding 2.5 parts of calcium hydroxide and 10 parts of deionized water to the mixed oil, mixing evenly to obtain the oil to be saponified;
[0091] S3, when the temperature of the saponified oil is raised to 90°C, stir and react for 2 hours to obtain saponified fat 1;
[0092] S4, heating the saponified fat 1 to 110°C to remove the water in the system; continuing to add 0.5 parts of calcium hydroxide and 3 parts of deionized water, and using ammonia water to adjust the pH of the system to 8, to obtain saponified fat 2;
[0093] S5, heating the saponified fat 2 to 210°C at a heating rate of 1.2°C / min, then adding the remaining 26 parts of base oil for cooling, and when the temperature drops to 135°C, maintaining the constant temperature for 0.5h to obtain the saponified fat; cooling the saponified fat to 90°C, and then adding a performance improver (1 part of nano copper emulsion, 0.5 parts of N-phenyl-α-naphthylamine and 0.5 parts of cyclohexane acid imidazoline) to obtain a calcium-based grease precursor;
[0094] S6. Grind the calcium-based grease precursor in a three-roll mill for three times to prepare a calcium-based grease.
[0095] Embodiment 18
[0096] The performance of the greases prepared from the metal salts prepared in Examples 1-17 and Comparative Examples 1 and 2 and the traditional lithium-based and calcium-based greases obtained in Comparative Examples 3 and 4 were tested. The cone penetration of the grease was measured according to GB / T 269-2023 "Method for Determination of Cone Penetration of Greases and Petroleum Greases"; the dropping point of the grease was measured using GB / T 3498-2008 "Method for Determination of Dropping Point of Grease over a Wide Temperature Range"; the oil separation of the steel mesh was measured according to SH / T 0324-92 "Method for Determination of Oil Separation of Grease on Steel Mesh (Static Method)"; in addition, the appearance of the grease and the time the grease retained its original properties after being immersed in a weak acid solution were visually inspected and recorded. The specific process for preparing the grease from the metal salt of the present invention is as follows: Figure 1 The test results of typical physical and chemical indicators are shown in Table 2.
[0097] The fiber structures of the greases prepared in Example 2, Example 8 and Comparative Example 3 were scanned by electron microscope. The results of SEM were as follows: Figure 2 , Figure 3 and Figure 4 shown.
[0098] Table 2 Test results of typical indicators of grease
[0099]
[0100] The test results in Table 2 show that the lubricating grease prepared by the present invention is brown and transparent in appearance. Figure 1The lithium-based lubricating grease prepared in Example 5 has a working cone penetration of 240-278 / 0.1 mm, a dropping point of 95-275°C, a steel mesh oil separation of 1.81%-4.55%, and maintains the properties of the grease within 10-26 days after being soaked in a weak acid solution. Examples 1-7 use weak alkali metal lithium salts to prepare lithium-based lubricating greases, and the properties are improved compared to Comparative Example 3 (lithium-based lubricating grease prepared by a traditional method). The results of Examples 1 and 2 show that by increasing the amount of base oil 500SN, the cone penetration of the obtained grease is reduced, the dropping point does not change much, and the oil separation is reduced; compared with Example 2, Example 3 replaces the metal salt with 12-hydroxy lithium stearate, and the cone penetration and oil separation are reduced. This may be due to the formation of intermolecular hydrogen bonds between the hydroxyl groups in the metal salt and the nano-tin self-healing material in the system, which improves the overall stability of the system; Examples 4-6 use 12-hydroxy sodium stearate and lithium metal salt to change the material ratio between the two. When the ratio of the two in Example 5 is 1:9, the overall performance of the grease is optimal. Example 7 is replaced with sodium stearate, and the cone penetration and oil separation are improved. In the preparation method of Comparative Example 1, all base oils are directly added to the reactor for reaction. Due to incomplete contact between the base oil and each component, the performance of the grease is reduced. The performance of the calcium metal salt grease prepared in Examples 8-15 is similar to or much better than that of Comparative Example 4 (calcium-based grease prepared according to the traditional method). In Examples 8-13, by compounding stearic acid, palmitic acid and sodium cyclohexane acid salts with metal calcium salts, the obtained grease has a cone penetration of 251-278 / 0.1mm, a dropping point of 248-264°C, and a steel mesh oil separation of 2.51%-2.66%. After being soaked in a weak acid solution, the grease still maintains its properties within 17-23 days. In Examples 14 and 15, the type of calcium salt and the ratio with sodium 12-hydroxystearate are changed, the cone penetration of the grease is reduced, the steel mesh oil separation is reduced, and the time for maintaining the grease properties after weak acid soaking is reduced compared with Examples 8-13. In Comparative Example 2, since calcium acetate is not added, the oil separation is increased, and calcium acetate has strong hygroscopicity, thereby ensuring the stable performance of the effects of other components. The grease prepared from barium-based metal salts in Examples 16 and 17 also has good comprehensive performance. Figure 2 , Figure 3 and Figure 4 The results show that the grease prepared by the present invention has a dense cross-linked network structure.
[0101] In summary, the present invention utilizes metal salts, adhesives and gelling agents to prepare various soap-based greases, simplifies the preparation process of the grease, and makes the preparation process green. At the same time, compared with lithium- and calcium-based greases prepared by traditional methods, the greases have better comprehensive properties, a high dropping point, less oil separation on the steel mesh, and good acid resistance.
[0102] Embodiment 19
[0103] Decyl acrylate CAS: 2156-96-9; Allyloxy nonylphenol polyoxyethylene (10) ether ammonium sulfate CAS: 184719-88-8;
[0104] Methyl methacrylate, acrylate, acrylic acid and methacrylate phosphate are uniformly mixed to obtain a mixed solution; the acrylate is decyl acrylate; the molar mass ratio of the four substances in the mixed solution is 1:1:1.2:1; the total amount of the four substances in the mixed solution is 94 parts; allyloxy nonylphenol polyoxyethylene (10) ether ammonium sulfate is dissolved in deionized water to obtain an ether ammonium sulfate aqueous solution with a mass fraction of 30%; the mixed solution is slowly added to the ether ammonium sulfate aqueous solution through a constant pressure dropping funnel, the dropping time is 30 minutes, and after the dropping is completed, it is homogenized and dispersed for 20 minutes to obtain a pre-emulsion; ammonium persulfate is mixed with deionized water to obtain to a 0.5% by mass ammonium persulfate solution; add 1 / 4 of the pre-emulsion into a four-necked flask filled with nitrogen, and add 4 parts of a 10% by mass sodium bicarbonate aqueous solution, raise the temperature to 75°C, and quickly drop 3 parts of the ammonium persulfate solution within 30 minutes, and when blue light appears, obtain an adhesive precursor; simultaneously drop the remaining pre-emulsion and 7 parts of the ammonium persulfate solution into the adhesive intermediate, the dropping time is 2 hours, and after the dropping is completed, keep the temperature for 1 hour, continue to raise the temperature to 90°C and react for 50 minutes to obtain an adhesive intermediate; the adhesive intermediate is cooled to room temperature, filtered and the pH is adjusted to 7 to obtain a phosphorus-containing acrylate adhesive.
[0105] Examples 20-25
[0106] Different from Example 19, the following preparation conditions are changed, as shown in Table 3.
[0107] Table 3 Preparation information of phosphorus-containing acrylate adhesive
[0108]
[0109] Embodiment 26
[0110] S1. In a normal pressure reactor, 55 parts of base oil 500SN and 13 parts of calcium metal salt were mixed evenly, and stirred at 500 rpm for 2 hours to obtain a uniform emulsion 1; in terms of mass ratio, the sodium cyclopentaneate:calcium cyclopentaneate in the calcium metal salt was 1:9;
[0111] S2, adding the remaining 37 parts of base oil 500SN to another reactor, adding 0.2 parts of polytetrafluoroethylene, and adding 0.8 parts of adhesive and 1 part of carboxymethyl cellulose gelling agent to obtain a mixture; in terms of mass ratio, the phosphorus-containing acrylate adhesive: trimethyl phosphate: triaminotriphenylthiophosphate in the adhesive is 8:1:1; the phosphorus-containing acrylate adhesive is prepared according to the method of Example 19; the mixture is stirred for 2 hours to obtain a uniform emulsion 2;
[0112] S3, transferring the uniform emulsion 1 to the uniform emulsion 2 to obtain a mixed emulsion; raising the temperature of the mixed emulsion to 60° C., stirring at a speed of 800 rpm for 3 hours, and performing a cross-linking reaction to obtain a uniform emulsion;
[0113] S4, heating the homogeneous emulsion to 200°C and degassing for 10 minutes to obtain a degassed emulsion;
[0114] S5, cooling the degassed emulsion to 85°C, maintaining the temperature for 0.5h, adding a performance improver (0.5 parts of nano copper emulsion, 0.5 parts of boron nitride, 0.5 parts of N-phenyl-α-naphthylamine and 0.5 parts of N-acyl sarcosine) to obtain a soap-based grease precursor; the nano copper emulsion boron nitride is an anti-wear agent; N-phenyl-α-naphthylamine is an antioxidant; and N-acyl sarcosine is a corrosion inhibitor;
[0115] S6. Grind the soap-based grease precursor in a three-roll mill for three times to prepare a soap-based grease prepared with a metal salt.
[0116] Examples 27-35
[0117] The detailed information of the preparation process of the embodiment is shown in Table 4.
[0118] Table 4 Detailed information on the preparation process of homogeneous emulsion II
[0119]
[0120] Embodiment 36
[0121] The difference from Example 26 is that the ratio of sodium 12-hydroxystearate to calcium palmitate in the calcium metal salt is 1:9.
[0122] Comparative Example 5
[0123] The difference from Example 26 is that no adhesive is added, the amount of polytetrafluoroethylene added is 0.5 parts, and the amount of gelling agent is 1.5 parts.
[0124] Comparative Example 6
[0125] The difference from Example 26 is that no adhesive is added, no polytetrafluoroethylene is added, and the gelling agent is 2.0 parts.
[0126] Embodiment 37
[0127] The greases prepared in Examples 26-36 and Comparative Examples 5 and 6 were tested for cone penetration, corrosion resistance and acid resistance. The corrosion resistance was tested in accordance with GB / T 5018-2008 "Test Method for Anticorrosion of Greases"; the cone penetration and acid resistance test methods were tested in accordance with the test methods of Example 18. The final test results are shown in Table 5.
[0128] Table 5 Test results of cone penetration, corrosion resistance and acid resistance
[0129]
[0130]
[0131] The working cone penetration of the grease prepared in the examples and comparative examples is 215-349 / 0.1mm. Except for comparative example 6, the corrosion resistance test results are all qualified. After being soaked in weak acid, the grease properties are maintained within 13-29. First, a phosphorus-containing acrylate adhesive is prepared, and then compounded with trimethyl phosphate or triethyl phosphate and triaminotriphenylthiophosphate to obtain an adhesive, and the obtained grease has good properties. In Examples 26-28, by changing the amount of polytetrafluoroethylene and the adhesive, the grease obtained has good corrosion resistance and acid resistance, and the working cone penetration is in the range of 264-293 / 0.1mm. After being soaked in a weak acid solution in Example 28, the grease properties are still maintained for 26 days, and the acid resistance is the best, but the cone penetration is increased compared with Example 26. Example 29 is compounded with triethyl phosphate to reduce the working cone penetration of the grease. In Examples 30-35, the preparation method of the phosphorus-containing acrylate adhesive used is changed. As shown in Example 33, the obtained grease has the best acid resistance, and the time for maintaining the grease properties after immersion in a weak acid solution is 29 days, and the working cone penetration is the lowest. By bonding methacrylic acid with long straight-chain acrylate, acrylic acid and long straight-chain phosphate to form an adhesive in an emulsion state, and adding polytetrafluoroethylene to play a role in thickening and corrosion protection, the obtained grease has excellent performance. In Comparative Example 5, no adhesive is added, and the working cone penetration increases; in Comparative Example 6, no polytetrafluoroethylene and adhesive are added, and the cone penetration is greatly increased, the corrosion resistance test result is unqualified, and the acid resistance decreases. In Example 36, sodium calcium cyclopentaneate and calcium cyclopentaneate are replaced by sodium 12-hydroxystearate and calcium palmitate. The acid resistance decreases compared with Example 26. The cyclopentane acid in the calcium salt has a good anti-rust effect, which helps to improve the stability of the grease after acid treatment.
[0132] Examples 38-48
[0133] Disperse 5 parts of sodium carboxymethyl cellulose in 200 parts of water to obtain a sodium carboxymethyl cellulose solution; add epoxy resin to the sodium carboxymethyl cellulose solution, heat it to 75°C, and stir to react for 3 hours to obtain a sodium epoxy cellulose solution; adjust the pH of the sodium epoxy cellulose solution to 2, add an organic acid, then add silicate and deionized water, raise the temperature to 85°C, stir to react for 5 hours, and obtain a modified methyl cellulose gelling agent after filtering and drying.
[0134] The lubricating grease was prepared according to the preparation method of Example 33, wherein 1 part of the carboxymethyl cellulose gelling agent was replaced by 0.6-0.8 parts of modified methyl cellulose and 0.2-0.4 parts of silane, and N-acyl sarcosine was replaced by sodium benzoate. The other preparation conditions remained unchanged.
[0135] The detailed information of the preparation process of modified methyl cellulose is shown in Table 6.
[0136] Table 6 Preparation information of modified methyl cellulose
[0137]
[0138]
[0139] Comparative Example 7
[0140] Different from Example 38, no gelling agent was added.
[0141] Embodiment 49
[0142] The greases prepared in Examples 38-48 and Comparative Example 7 were tested for dropping point, oil separation and water resistance. The dropping point and steel mesh oil separation were measured according to the method of Example 18, and the water runoff loss was measured according to SH / T 010-2004 "Method for Determination of Water Runoff Resistance of Lubricating Grease". The final test results are shown in Table 7.
[0143] Table 7 Test results of dropping point, oil separation and water resistance of grease
[0144]
[0145] Combined with the results in Table 7, the dropping point of the grease prepared by the present invention is 226-314°C, the oil separation of the steel mesh is 1.48%-4.62%, and the water loss is 0.27%-1.29%. By dispersing methyl cellulose in water to form a cellulose solution, the epoxy resin opens the epoxy bond under high temperature conditions and condenses with the hydroxyl groups on the surface of the methyl cellulose, and then the epoxy resin and the methyl cellulose are connected by chemical bonds, one end of the organic acid is connected to the methyl cellulose, and the other end is coupled with the hydrolyzed silicate to form modified methyl cellulose. The results of Examples 38 and 39 show that the final grease has a good effect when the amount of water added during hydrolysis is 4.2 parts. The results of Examples 39 and 40 show that changing the type of epoxy resin increases the dropping point of the grease. The BADGE of Example 40 contains multiple benzene ring structures, which improves the rigidity of the grease while also improving the high temperature resistance. Example 41 determines the type of silicate as ethyl silicate, and the oil separation is reduced compared with Example 40. Examples 41-44 change the type of organic acid, wherein Example 44 uses hexadecanediol as the organic acid, and the highest dropping point is 295°C. Grease is obtained by using modified methyl cellulose in combination with silane, and Examples 44-46 change the type of silane, and Example 46 adds triethoxyoctadecanesilane to obtain the highest dropping point of the grease, and the silicon-oxygen bond and long-chain alkane improve the high temperature resistance of the grease, and Example 44 adds n-octyltriethoxysilane to obtain the lowest oil separation of the grease. Examples 46-48 change the amount of modified methyl cellulose and silane, and the water loss of the grease is low, at 0.27%-0.45%. The silane in the modified methyl cellulose and the silane used in combination work together to improve the water resistance of the grease.
[0146] Examples 50-61
[0147] Disperse nano-titanium dioxide and ionic liquid in 100 mL of anhydrous ethanol, and ultrasonicate for 20 min to obtain a TiO2-loaded ionic liquid precursor; the total amount of nano-titanium dioxide and ionic liquid is 30 parts; the amount ratio of nano-titanium dioxide to ionic liquid is 19:1; nano-titanium dioxide is mesoporous; place the TiO2-loaded ionic liquid precursor in an oven at 80°C and dry for 24 h to obtain a TiO2-loaded ionic liquid;
[0148] A metal salt lithium-based grease was prepared according to the method of Example 5, wherein the amount and type of each component of the performance improver were changed, and the components of the performance improver included 1 part of nano copper emulsion, 0-0.7 parts of antioxidant 1 and 0.3-1 parts of antioxidant 2; antioxidant 1 was TiO2-loaded ionic liquid; antioxidant 2 was butylhydroxymethoxybenzene; the total amount of antioxidant 1 and antioxidant 2 was 1.0 part; and the anticorrosive agent cyclohexane imidazoline was replaced with petroleum sodium sulfonate T702. The other preparation steps and methods were consistent with those of Example 5, and the specific preparation information is shown in Table 8.
[0149] Embodiment 62
[0150] The anti-oxidation performance of the greases prepared in Examples 50-61 and Comparative Example 8 was tested. The test method was based on SH / T0719-2002 "Determination of oxidation induction period of lubricating oil (pressure differential scanning calorimetry)". The test results are shown in Table 8.
[0151] Table 8 Preparation, dosage and antioxidant test results of antioxidants in performance improvers
[0152]
[0153]
[0154] The grease prepared in the examples and comparative examples has an oxidation induction time of 16.9-35.8 min under the test condition of 180°C. The test results of Examples 50-53 show that changing the type of ionic liquid loaded on nano-titanium dioxide changes the antioxidant properties. Examples 51-53 use imidazole ionic liquids for loading, and their antioxidant effect is better than the pyridinium ionic liquid of Example 50. The grease obtained from the ionic liquid composed of anions of methylsulfonyl in Example 53 has the longest oxidation induction time of 30.1 min. By loading ionic liquids on mesoporous nano-titanium dioxide, on the one hand, the overall specific surface area of the antioxidant is increased, free radicals are more easily captured, and titanium dioxide itself has a stable and lasting antioxidant effect. On the other hand, the cation and anion structure in the ionic liquid further enhances the antioxidant effect; the obtained TiO2-loaded ionic liquid is used in conjunction with an organic antioxidant to increase the oxidation induction time. In Examples 53-56, the amounts of nano-titanium dioxide and ionic liquid were changed, and the anti-oxidation effects of the obtained greases were different. In Example 54, when the ratio of the two was 9:1, the oxidation induction time was the longest. In Example 57, the amount of antioxidant one was increased, and the amount of antioxidant two was reduced, and the anti-oxidation effect of the grease was improved. In Examples 54 and 58-61, TiO2-loaded ionic liquid antioxidant one and antioxidant two were used in synergy, and the type of organic antioxidant two was changed, and the obtained grease had good anti-oxidation effect. In Comparative Example 8, only 1.0 part of butylhydroxymethoxybenzene organic antioxidant was used, and the oxidation induction time was only 16.9 min. In summary, the TiO2-loaded ionic liquid prepared by the present invention is used together with an organic antioxidant to prepare a grease, and the obtained grease has excellent anti-oxidation properties.
[0155] Embodiment 63
[0156] Disperse 3 parts of cellulose nanocrystals in 65 parts of deionized water and 35 parts of anhydrous ethanol, stir evenly to obtain a cellulose nanocrystal suspension; raise the temperature to 60°C, add 5 parts of sodium butyrate and stir for 5 hours, adjust the pH to 4.5 when the temperature drops to 25°C, dialyze with distilled water and freeze-dry to obtain freeze-dried cellulose nanocrystals; disperse the freeze-dried cellulose nanocrystals in 100 parts of deionized water, raise the temperature to 90°C, add 1.2 parts of potassium stannate trihydrate, stir and react for 3 hours to obtain a tin-containing cellulose nanocrystal solution; after the tin-containing cellulose nanocrystal solution drops to 25°C, add 6.5 parts of sodium periodate were added, stirred for 24 hours in a dark environment, and then 15 parts of ethylene glycol solution were added, and dialyzed to obtain a tin-containing oxidized cellulose nanocrystal solution; 4.7 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 3.5 parts of N-hydroxysuccinimide were added to the tin-containing oxidized cellulose nanocrystal solution, and then 8.2 parts of 5-(2-amino-ethyl)-2-hydroxybenzoic acid were added to obtain a graft precursor; the graft precursor was heated to 50° C., stirred for reaction under nitrogen protection for 10 hours, and dialyzed through a 10 kDa dialysis bag to obtain a graft solution;
[0157] Dissolve 15 parts of chitosan in 200 mL of 0.5% acetic acid solution under stirring to obtain a chitosan solution; dissolve 3.8 parts of N-hydroxysuccinimide and 4.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide in 50 mL of methanol to obtain a catalytic mixture; add the catalytic mixture to the chitosan solution, add 6.5 parts of 4-carboxynaphthalene-1-boric acid, increase the temperature to 80°C, and stir the reaction for 20 hours to obtain a phenylboric acid chitosan solution; dialyze and dry the phenylboric acid chitosan solution to obtain phenylboric acid chitosan;
[0158] Add 10 parts of phenylboronic acid chitosan to 300 parts of deionized water, and raise the temperature to 80°C to obtain solution 1; add the graft solution to solution 1, and add 0.6 parts of polyvinyl alcohol and mix well to obtain solution 2; stir solution 2 to react for 7 hours, cool it down, filter it, and dry it to obtain the nano-tin self-healing material.
[0159] Embodiment 64
[0160] The difference from Example 63 is that 6.5 parts of 4-carboxynaphthalene-1-boronic acid are replaced by 7.3 parts of 4'-(carboxy)biphenyl-4-boronic acid.
[0161] Embodiment 65
[0162] The difference from Example 63 is that 6.5 parts of 4-carboxynaphthalene-1-boric acid are replaced by 6.3 parts of 3,5-diboronic acid benzoic acid.
[0163] Embodiment 66
[0164] The difference from Example 63 is that the amount of 5-(2-amino-ethyl)-2-hydroxybenzoic acid added is 7.5 parts.
[0165] Embodiment 67
[0166] Different from Example 63, the added amount of 5-(2-amino-ethyl)-2-hydroxybenzoic acid was 9.0 parts.
[0167] Embodiment 68
[0168] 10 parts of nano copper were added into a ball mill, and 70 parts of methacrylate copolymer emulsion were added thereto, and the mixture was ground at a rotation speed of 300 rpm for 5 hours to obtain a nano copper emulsion.
[0169] Embodiment 69
[0170] A metal salt lithium-based grease was prepared according to the method of Example 5, wherein the amount and type of each component of the performance improver were changed, and the components of the performance improver included 0.3 parts of the nano copper emulsion prepared by the method of Example 69, 0.7 parts of the nano tin self-healing material prepared by the method of Example 63, 0.6 parts of the TiO2-loaded ionic liquid prepared by the method of Example 54, and 0.4 parts of thiadiazole derivatives. 1 part of the carboxymethyl cellulose gelling agent was replaced by 1 part of the modified methyl cellulose gelling agent prepared by Example 42.
[0171] Examples 70-73
[0172] Different from Example 69, the nano-tin self-healing material is prepared by the methods of Examples 64-67 in sequence.
[0173] Embodiment 74, 75
[0174] Different from Example 69, the nano-tin self-healing material is replaced by boron nitride and sodium cyclopentaneate in sequence.
[0175] Comparative Example 9
[0176] Different from Example 69, the amount of nano copper emulsion used is 1.0 part, and no nano tin self-healing material is added.
[0177] Embodiment 76
[0178] The greases prepared in Examples 69-75 and Comparative Example 9 were tested for extreme pressure and anti-wear properties. The P of the grease was measured by a four-ball machine test. B For the value, please refer to GB / T 3142-2019 "Determination of load-bearing capacity of lubricants - Four-ball method"; for the anti-friction test, refer to SH / T 0204-92 "Test method for anti-wear performance of grease (four-ball machine method)". The final test results are shown in Table 9.
[0179] Table 9 Test results of extreme pressure and anti-wear properties of grease
[0180]
[0181] As shown in Table 9, the P values of the lubricating greases prepared in the embodiments of the present invention and the comparative examples are B The wear scar diameter is 0.35-0.62 mm under the test conditions of 75°C, 392N pressure and 1200rpm. By mixing cellulose nanocrystals with tin-containing metal salts and oxidizing the cellulose nanocrystals, the six-membered ring in the cellulose structure is broken, and the corresponding hydroxyl position forms a two-carbonyl structure. The amino group of 5-(2-amino-ethyl)-2-hydroxybenzoic acid and the hydroxyl group of the oxidized cellulose nanocrystals undergo an aminohydroxylation reaction to obtain a grafted product; under the action of a catalyst, chitosan and phenylboronic acid undergo an amide condensation reaction to obtain phenylboronic acid chitosan; phenylboronic acid chitosan and the grafted product are covalently linked by a Mannich reaction, and the covalently linked product condenses with a molecule of boric acid in phenylboronic acid chitosan, and finally polyvinyl alcohol is cross-linked with the hydroxyl group in the system to obtain a nano-tin self-healing material. The nano-tin self-repairing material contains reversible dynamic bonds. When the grease is under strong pressure, the nano-tin self-repairing material can achieve self-healing effect by forming and breaking hydrogen bonds. After the hydrogen bonds are damaged and broken, they re-form new hydrogen bonds with chitosan and cellulose nanocrystals. In addition, the metal tin forms a metal coordination bond in the system, so that the nano-tin self-repairing material has a self-repairing effect. Therefore, when used in grease together with the nano-copper emulsion, the extreme pressure and wear resistance of the grease are improved. In Examples 69-71, the type of phenylboronic acid is changed to achieve different extreme pressure and wear resistance effects. Example 70 uses 4'-(carboxyl)biphenyl-4-boric acid for reaction, P B The highest is 981N. Compared with other examples, the number of introduced benzene rings is increased, and the compressive resistance of the grease is improved. The results of Examples 69, 72, and 73 show that the extreme pressure and wear resistance of the grease change by changing the content of the grafted compound. In Examples 74 and 75, the nano-tin self-healing material is replaced with boron nitride and sodium cyclopentaneate, and the extreme pressure and wear resistance are reduced. Comparative Example 9 uses only nano-copper emulsion, and the grease obtained has the lowest extreme pressure, P B It is only 491N, and the anti-wear performance is the worst compared with the examples.
[0182] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A lubricating grease prepared using a metal salt, characterized in that: The lubricating grease is prepared from the following components in parts by weight: Base oil 86-92 parts; 10-13 parts of metal salt; Polytetrafluoroethylene ≤ 0.2 parts (excluding 0 parts); Adhesive ≤ 0.8 parts (excluding 0 parts); Gelation reagent ≤ 2 parts (excluding 0 parts); 2 parts of performance improver; The adhesive comprises phosphorus-containing acrylate adhesive, trimethyl phosphate and triaminotriphenylthiophosphate; the phosphorus-containing acrylate adhesive is prepared from methyl methacrylate, acrylic acid phosphate, acrylic acid and acrylic acid ester; The gelling agent comprises carboxymethyl cellulose, modified methyl cellulose and silane; the modified methyl cellulose is prepared by adding epoxy resin to a sodium carboxymethyl cellulose solution, heating the solution to 75°C, stirring and reacting for 3 hours to obtain a sodium epoxy cellulose solution; the pH of the sodium epoxy cellulose solution is adjusted to 2, an organic acid is added, and then silicate and deionized water are added, the temperature is increased to 85°C, stirring and reacting for 5 hours, and filtering and drying to obtain the solution; The structures of the silane and the silicate are shown below: ; Wherein R4 is one of methoxy, ethoxy, vinyl, octyl, and octadecyl; R5, R6, and R7 are each one of methyl and ethyl; The performance improvers include antioxidants, anti-wear agents and anti-corrosion agents; The antioxidant includes antioxidant 1 and antioxidant 2; The anti-wear agent comprises nano copper emulsion, nano tin self-repairing material, boron nitride and sodium naphthenate.
2. The lubricating grease prepared by using metal salt according to claim 1, characterized in that: The base oil is selected from one of 350SN and 500SN; the metal salt is one or a combination of two or three of lithium stearate, 12-hydroxy lithium stearate, 12-hydroxy sodium stearate, sodium stearate, calcium stearate, 12-hydroxy calcium stearate, sodium palmitate, calcium palmitate, sodium naphthenate, calcium naphthenate, calcium borate, calcium acetate, barium stearate, and 12-hydroxy barium stearate.
3. The lubricating grease prepared by using a metal salt according to claim 1, characterized in that: The acrylic acid ester is any one of decyl acrylate, dodecanol acrylate and octadecyl acrylate; the acrylic acid phosphate is any one of methacrylic acid phosphate, polyethylene glycol methacrylic acid phosphate, 10-(2-methacryloyloxy)monodecyl phosphate and 2-methyl-2-acrylic acid-2-(phosphonooxy)ethyl ester; in terms of molar mass ratio, the methyl methacrylate: the acrylic acid: the acrylic acid: the acrylic acid phosphate is 1:1:1-1.2:1; the total amount of the methyl methacrylate, the acrylic acid, the acrylic acid and the acrylic acid phosphate is 94-125 parts.
4. The lubricating grease prepared by using a metal salt according to claim 1, characterized in that: The silane is any one of n-octyltriethoxysilane, vinyltrimethoxysilane and triethoxyoctadecylsilane; the amount of the silane is 0.2-0.4 parts; the epoxy resin is any one of RDGE and BADGE; the amount of the epoxy resin is 22-34 parts; the organic acid is any one of glutaric acid, azelaic acid, sebacic acid and hexadecanedioic acid; the amount of the organic acid is 13-28 parts; the silicate is any one of methyl silicate and ethyl silicate; the amount of the silicate is 15-21 parts; the amount of deionized water is 4.0-4.2 parts.
5. The lubricating grease prepared by using metal salt according to claim 1, characterized in that: The antioxidant one is obtained by loading ionic liquid with nano-titanium dioxide; the dosage of the antioxidant one is 0-0.7 parts; the ionic liquid is any one of [C8MPy]PF6, [C16Mim]PF6, [C16Mim]BF4 and [C12M2Im]NTf2; the dosage ratio of the nano-titanium dioxide and the ionic liquid is 4-19:1-3; the dosage of the antioxidant two is 0.3-1 parts.
6. The lubricating grease prepared by using metal salt according to claim 1, characterized in that: The second antioxidant is any one of butylated hydroxymethoxybenzene, N-phenyl-α-naphthylamine, alkylated phenyl-α-naphthylamine, benzotriazole derivatives, thiadiazole derivatives and butylated hydroxymethoxybenzene.
7. The lubricating grease prepared by using metal salt according to claim 1, characterized in that: The anticorrosive agent is any one of sodium petroleum sulfonate, imidazoline cyclohexane acid, N-acyl sarcosine and sodium benzoate.
8. The lubricating grease prepared by using metal salt according to claim 1, characterized in that: The preparation method of the nano copper emulsion is as follows: 10 parts of the nano copper emulsion is added into a ball mill, 70 parts of the methacrylate copolymer emulsion is added thereto, and the mixture is ground at a rotation speed of 300 rpm for 5 hours to obtain the nano copper emulsion.
9. The lubricating grease prepared by using metal salt according to claim 1, characterized in that: The preparation method of the nano-tin self-repairing material is as follows: The cellulose nanocrystals are dispersed in deionized water and anhydrous ethanol, and stirred to obtain a cellulose nanocrystal suspension; the temperature is raised to 60°C, and sodium butyrate is added and stirred, and the pH is adjusted to 4.5 when the temperature drops to 25°C, and distilled water is used for dialyzing and freeze-drying to obtain freeze-dried cellulose nanocrystals; the freeze-dried cellulose nanocrystals are dispersed in deionized water, the temperature is raised to 90°C, and potassium stannate trihydrate is added, and the reaction is stirred for 3 hours to obtain a tin-containing cellulose nanocrystal solution; after the tin-containing cellulose nanocrystal solution drops to 25°C, sodium periodate, stirring for 24 hours under light-proof conditions, then adding ethylene glycol solution, and dialyzing to obtain a tin-containing oxidized cellulose nanocrystal solution; adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide to the tin-containing oxidized cellulose nanocrystal solution, and then adding 7.5-9.0 parts of 5-(2-amino-ethyl)-2-hydroxybenzoic acid to obtain a graft precursor; raising the temperature of the graft precursor to 50° C., stirring and reacting under nitrogen protection for 10 hours, and dialyzing through a dialysis bag to obtain a graft solution; Dissolving chitosan in an acetic acid solution under stirring to obtain a chitosan solution; dissolving the N-hydroxysuccinimide and the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide in methanol to obtain a catalytic mixed solution; adding the catalytic mixed solution to the chitosan solution, and then adding 6.3-7.3 parts of phenylboric acid, raising the temperature to 80° C., and stirring for 20 hours to obtain a phenylboric acid chitosan solution; dialyzing and drying the phenylboric acid chitosan solution to obtain phenylboric acid chitosan; the phenylboric acid is any one of 4-carboxynaphthalene-1-boric acid, 4'-(carboxy)biphenyl-4-boric acid and 3,5-diboric acid benzoic acid; The phenylboronic acid chitosan is added into deionized water, and the temperature is raised to 80° C. to obtain solution 1; the graft solution is added into solution 1, and polyvinyl alcohol is added and mixed evenly to obtain solution 2; the solution 2 is stirred and reacted for 7 hours, and after cooling, it is filtered and dried to obtain the nano-tin self-healing material.
10. A method for preparing a lubricating grease using a metal salt, characterized in that: The components of the grease prepared by using metal salts are as shown in claim 1; the preparation method comprises the following steps: S1: In a normal pressure reactor, part of the base oil and the metal salt are mixed evenly, and stirred at 500 rpm for 2 h to obtain a uniform emulsion 1; S2: adding the remaining base oil into another reactor, adding polytetrafluoroethylene, an adhesive and a gelling agent to obtain a mixture; stirring the mixture for 2 hours to obtain a uniform emulsion 2; S3: transferring the uniform emulsion 1 to the uniform emulsion 2 to obtain a mixed emulsion; raising the temperature of the mixed emulsion to 60° C., stirring at a speed of 800 rpm for 3 hours, and performing a cross-linking reaction to obtain a uniform emulsion; S4: heating the uniform emulsion to 200° C. and degassing for 10 min to obtain a degassed emulsion; S5: cooling the degassed emulsion to 85° C., maintaining the temperature for 0.5 h, adding a performance improver, and obtaining a soap-based grease precursor; S6, grinding the soap-based grease precursor in a three-roll mill for three times to prepare the grease prepared from the metal salt; The grease comprises the base oil, the metal salt, the polytetrafluoroethylene, the adhesive, the gelling agent and the performance improver; the grease is brown and transparent in appearance; the working cone penetration of the grease is 240-278 / 0.1mm, the dropping point is 95-275°C, and the oil separation of the steel mesh is 1.81%-4.55%; by adding the adhesive, the working cone penetration of the grease is 215-349 / 0.1mm, the corrosion resistance test is qualified, and the grease maintains the grease properties within 18-29 days after being soaked in weak acid; by adding the gelling agent, the dropping point of the grease is 226-314°C, the oil separation of the steel mesh is 1.48%-4.62%, and the water loss is 0.27%-1.29%; under the test condition of 180°C, the PDSC oxidation induction time of the grease is 16.9-35.8min; P B The wear force is 491-981N, and the wear scar diameter is 0.35-0.62mm.
Citation Information
Patent Citations
A composite grease and its preparation method
CN110616102B
An antioxidant composition for lithium-based greases
CN113913228B
Composite lithium-calcium based lubricating grease and preparation method thereof
CN104560313A
Environment-friendly lubricating grease with high lubricating property and preparation method thereof
CN109536260A